Knowledge Management as a Strategy for Achieving High Entrepreneurial Performance and Competitiveness - Chinonye , Moses Love (African Journal of Education,Science and Technology (AJEST), 2025)
Enterprises operate in a dynamic environment and to remain relevant and competitive, there is need for adequate knowledge of their environment and effective management of resources for the achievement of high entrepreneurial performance. This paper focused on k nowledge management as a strategy for achieving high entrepreneurial performance and competitiveness . It sought to find out if there is significant relationship between variables used in measuring knowledge management (independent variable), and entrepreneurial performance and competitiveness (dependent variables). Survey research was used in a cross sectional design method through the use of self-administered questionnaires to some selected enterprises in Ota, Ogun State. The data collected were subjected to simple regression analysis to measure the various effects of the independent variables on the dependent variables. The result s of the analysis showed that the entrepreneur‟s ability to evaluate and utilize knowledge has positive relationship with the enterprise competitive position. The result also showed that the enterprise learning, knowledge and skills have positive relationship with the organizational product development. Based on these findings, the study among others recommends that entrepreneurs should not only embrace knowledge management but must continue to improve on their ability to evaluate and utilize knowledge i n order to enhance their performance and competitiveness in their business environment.